Research into psychomotor differences in adolescents with childhood cerebral palsy who participate in adaptive sports and those who do not - Rubtsova N.O. ,; Artamonova T.V. ,; Spirina I.K. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the characteristics of psychomotor development in adolescents with cerebral palsy who participate and do not participate in adaptive sports. Methods and structure of the study. 20 adolescents aged 12-14 with cerebral palsy (10 sledge hockey players from the CSKA team and 10 students from Boarding School No. 17, Moscow) participated in the scientific study conducted in November 2024. All respondents had been diagnosed with spastic diplegia and had normal intellectual abilities. To assess the level of psychomotor development in adolescents with cerebral palsy who participate in sports and those who do not, the following indicators were studied: reaction time to light, reaction time to sound, reaction time to choice, duration of an individual minute, and the tapping test. The PsychoTest hardware and software complex was used. Results and conclusions. It has been found that sledge hockey has a positive effect on the psychomotor development of adolescents with cerebral palsy, contributing to improved psycho-emotional health. Athletes with cerebral palsy have a higher level of ability to regulate their actions based on the information they receive and their concentration compared to their peers, the productive quality of their nervous system is higher, and their psychological state is much closer to that of their typical peers.